Sustainable design of past-rural architecture in the present urban-tropical environment - FX Teddy Badai Samodra (Institut Teknologi Sepuluh Nopember, 2017)
With large open space, traditional houses as representative of rural architecture, have been designed in the past in sufficient air flow. However, nowadays, they fight to accommodate unsupportive environment; high density neighborhoods and global warming effect. This research studies adaptation method and concept of sustainable design of the rural architecture in urban environment of tropical climate. Simultaneous direct measurement and occupant interview were conducted on 19 buildings and 71 respondents. Ecotect Analysis and CFD Fluent program were also used to obtain the proposed model. The results highlighted that by active and passive ventilation method, the occupants respond their urban environment. Moreover, the sustainable design can be reached by raising the floor and roof in order to give higher potency of cooler sufficient air movement through openings and shading. Providing solar chimney as vertical ventilation with sufficient ceiling fan works is also proposed.